Design, Fabrication, and Characterization of a PMN-PT based Ultrasound Transducer - Zaidi, Syed Turab Haider; Kim, Dong Hun; Shah, Muhammad Ali; Lee, Young Jin; Lee, Byung Chul; Hur, Shin (2025 IEEE International Conference on Flexible and Printable Sensors and Systems (FLEPS), 2025)
This study introduces a flexible and stretchable ultrasonic transducer array (UTA) featuring a 5x4 element layout. The array combines a 1-3 piezoelectric composite with serpentine electrodes, all encapsulated within a biocompatible elastomer, allowing for independent excitation of each element. Initial testing reveals a resonant frequency of 6.0 MHz and a penetration depth of up to 30 mm, indicating effective acoustic transmission. The serpentine electrodes accommodate up to 30% tensile strain, maintaining reliable electrical connectivity and mechanical stability under deformation. The array's performance was further validated through acoustic beam transmission and target localization using the CIRS Model ATS 539 Multi-Purpose Phantom.